Congenital disorders of glycosylation with defective fucosylation - Huellen, Andreas; Falkenstein, Kristina; Weigel, Corina; Huidekoper, Hidde; Naumann-Bartsch, Nora; Spenger, Johannes; Feichtinger, Rene G.; Schaefers, Jacqueline; Frenz, Stephanie; Kotlarz, Daniel; Momen, Tooba; Khoshnevisan, Razieh; et al. (Journal of Inherited Metabolic Disease, 2021)
Fucosylation is essential for intercellular and intracellular recognition, cell-cell interaction, fertilization, and inflammatory processes. Only five types of congenital disorders of glycosylation (CDG) related to an impaired fucosylation have been described to date: FUT8-CDG, FCSK-CDG, POFUT1-CDG SLC35C1-CDG, and the only recently described GFUS-CDG. This review summarizes the clinical findings of all hitherto known 25 patients affected with those defects with regard to their pathophysiology and genotype. In addition, we describe five new patients with novel variants in the SLC35C1 gene. Furthermore, we discuss the efficacy of fucose therapy approaches within the different defects.
CRIS-Team Scopus Importer:2021-09-24
Keywords: CDG; coarse facial features; developmental delay; epilepsy; fucosylation; intellectual disability; neutrophilia